Molecular Theory of Phase Separation in Nematic Liquid Crystals Doped with Spherical Nanoparticles. Issue 7 (3rd March 2014) - Osipov, Mikhail A.; Gorkunov, Maxim V.
Abstract A molecular‐statistical theory is developed, which enables one to describe the nematic–isotropic phase transition in liquid crystals doped with spherical nanoparticles taking into account the effects of phase separation. It has been shown that in the case of strong interaction between nanoparticles and mesogenic molecules the nematic nanocomposite possesses a number of unexpected properties. In particular, the nematic–isotropic co‐existence region appears to be very broad, and the system either undergoes a direct transition from the isotropic phase into the phase‐separated state, or undergoes the transition into the homogeneous nematic phase first and then phase‐separates at a lower temperature. Phase separation does not occur at all if the concentration of the nanoparticles is sufficiently low, and in some cases it takes place only within a finite region of nanoparticle concentration. A number of temperature–concentration phase diagrams is presented and the molar fractions of nanoparticles in the co‐existing isotropic and nematic phases are calculated numerically as functions of temperature.